2017
DOI: 10.1002/ejp.1044
|View full text |Cite
|
Sign up to set email alerts
|

Fear of pain changes movement: Motor behaviour following the acquisition of pain‐related fear

Abstract: Fear of pain changes movement: Movements associated with pain are performed faster, with more force and higher accuracy than movements that are not associated with pain. These changes can inform us how fear of pain translates into avoidance and escape behaviour, two important constructs in the maintenance of chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 24 publications
4
58
1
Order By: Relevance
“…This result is compatible with a recent study that used a fear of pain conditioning paradigm and tested circular arm movements (Karos et al . ), who suggest that this result reflects a ‘get it over and done with’ motor strategy when movement‐related pain cannot be avoided.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…This result is compatible with a recent study that used a fear of pain conditioning paradigm and tested circular arm movements (Karos et al . ), who suggest that this result reflects a ‘get it over and done with’ motor strategy when movement‐related pain cannot be avoided.…”
Section: Discussionmentioning
confidence: 95%
“…Parallel to this, another recent study explored the effect of pain anticipation on behavioural motor changes, using a pain‐related fear conditioning paradigm (Karos et al . ). Results revealed that movements associated with pain are performed faster, more forcefully and more accurately than movements without pain.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…First, kinesiophobia alters how people move, possibly with the initial goal to avoid pain. It causes adjustments of motor behaviour which affects the performance of actions related to the management and control of pain and pain-related disability 22. Second, the processing of pain and pain-related information in people with CMP could be related to how kinesiophobia is perceived 23.…”
Section: Introductionmentioning
confidence: 99%